UPLC-MS profiling of low molecular weight phlorotannin polymers in Ascophyllum nodosum, Helvetia canaliculata and Fucus spiralis - Tierney, Michelle S.; Soler-Vila, Anna; Rai, Dilip K.; Croft, Anna K.; Brunton, Nigel P.; Smyth, Thomas J. (Springer, 2014)
Phlorotannins are a group of complex polymers, found in particular brown macroalgae, composed solely of the monomer phloroglucinol (1,3,5-trihydroxybenzene). Their structural complexity arises from the number of possible linkage positions between each monomer unit. This study aimed to profile the phlorotannin metabolite composition and the complexity of isomerisation present in brown macroalgae Ascophyllum nodosum, Pelvetia canaliculata and Fucus spiralis using UPLC-MS utilising a tandem quadrupole mass spectrometer. Phlorotannin-enriched fractions from water and aqueous ethanol extracts were analysed by UPLC-MS performed in multiple reaction monitoring mode to detect molecular ions consistent with the molecular weights of phlorotannins. Ascophyllum nodosum and P. canaliculata appeared to contain predominantly larger phlorotannins (degree of polymerisation (DP) of 6–13 monomers) compared to F. spiralis (DP of 4–6 monomers). This is the first report observing the complex chromatographic separation and metabolomic profiling of low molecular weight phlorotannins consisting of more than ten monomers. Extracted ion chromatograms, for each of the MRM transitions, for each species were analysed to profile the level of isomerisation for specific molecular weights of phlorotannins between 3 and 16 monomers. The level of phlorotannin isomerisation within the extracts of the individual macroalgal species differed to some degree, resulting in substantially different numbers of phlorotannin isomers for particular molecular weights. A similar UPLC-MS/MS separation procedure, as outlined in this study, may be used in the future as a means of screening the metabolite profile of macroalgal extracts, therefore, allowing extract consistency to be monitored for standardisation purposes.